Mapping of 2D contact perturbations by electrons on a helium film - Teske, E.; Wyder, P.; Leiderer, P.; Shikin, V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
A promising way to investigate 2D contact phenomena is proposed. This method is based on the idea of depositing surface state electrons (SSE) on a thin layer of liquid helium covering the surface of a solid sample containing a 2D charge carrier system. The density of SSE adjusts to screen contact-induced perturbations of the electrostatic potential across the sample. As a result, the helium layer thickness varies due to the variation of the electrostatic pressure, thus providing a map. This map may be read off interferometrically by a technique already employed for the investigation of multi-electron dimples on helium. We have realized this mapping for a structured electrode as a test sample to demonstrate the resolution of the method.